EFEKTIFITAS PELATIHAN LABORATORIUM VIRTUAL SEBAGAI MEDIA PEMBELAJARAN BAGI GURU KIMIA - Achmad Lutfi; Sukarmin Sukarmin (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2019)
EFFECTIVITY OF VIRTUAL LABORATORY TRAINING AS A LEARNING MEDIA FOR CHEMISTRY TEACHERSAchmad Lutfi, SukarminUniversitas Negeri Surabaya, Indonesia achmadlutfi@unesa.ac.idAbstractThe study aims to determine the level of training achievement using virtual laboratories for chemistry teachers on the ability of teachers to use virtual laboratories and the achievement of objectives in learning chemistry using virtual laboratories. The training was conducted for chemistry teachers who were members of the City and District High School Chemistry Teachers' Working Group (MGMP). During the study, the teachers were trained in how to install, operate virtual laboratories, and conduct experiments with virtual laboratories. At the end of the activity, an ability test was conducted using a virtual laboratory, giving questionnaires to participants and assigning participant assignments in the form of lesson plans (RPP) with the use of virtual laboratories as learning media. The data obtained showed that 90% of the participating teachers had been able to use virtual laboratory programs, including installing, operating, and conducting experiments with virtual laboratories. 82-100% of the participants found it useful to participate in the activities, and the compiled lesson plans showed that the participants were able to use the virtual laboratory as a medium for chemistry learning with a percentage of 85% -100%, and students gave positive responses and good learning outcomes after participating in chemistry learning with use of virtual laboratories. AbstrakPenelitian bertujuan mengetahui tingkat ketercapaian pelatihan menggunakan laboratorium virtual bagi guru kimia terhadap kemampuan guru menggunakan laboratorium virtual dan ketercapaian pembelajaran kimia dengan menggunakan laboratorium virtual. Pelatihan dilakukan terhadap guru kimia yang tergabung pada Musyawarah Guru Mata Pelajaran Kimia Sekolah Menengah Atas Kota dan Kabupaten Kediri. Selama penelitian dilatihkan cara menginstal , mengoperasikan laboratorium virtual dan melakukan percobaan dengan laboratorium virtual. Pada akhir kegiatan dilakukan tes kemampuan menggunakan laboratorium virtual, pemberian angket kepada peserta dan pemberian tugas peserta berupa pembuatan rencana pelaksanaan pembelajaran (RPP) dengan pemanfaatan laboratorium virtual sebagai media pembelajaran. Data yang diperoleh menunjukkan 90% guru peserta telah mampu menggunakan program laboratorium virtual, meliputi: menginstal, mengoperasikan, dan melakukan percobaan dengan laboratotium virtual. Sebesar 82-100 % peserta merasa bermanfaat mengikuti kegiatan dan RPP yang disusun memperlihatkan bahwa peserta sudah dapat memanfaatkan laboratorium virtual sebagai media pembelajaran kimia dengan prosentasi 85%-100%, serta peserta didik memberikan tanggapan positif dan hasil belajar yang baik setelah mengikuti pembelajaran kimia dengan penggunaan laboratorium virtual.